Legitimacy Strategies in Political Statements: A Critical Pragmatic Study of The Discourse of National Grief over The Deaths of Three Indonesian Soldiers in The UN Peacekeeping Mission in Lebanon - Puji Laksono (UIN Salatiga, 2026)
Based on the theoretical framework of legitimacy strategies, this study uses the Critical Discourse Analysis approach combined with a critical pragmatic perspective to examine how President Prabowo's political statements regarding national mourning over the deaths of three soldiers in the UN peacekeeping mission in Lebanon are constructed and how these constructions interact with, reproduce, or negotiate broader social, ideological, and cultural structures. There are five key interrelated legitimacy strategies—authorization, rationalization, moral evaluation, mythosis, and unification—that are realized through pragmatic mechanisms such as implication, presupposition, and speech acts. The study found that political statements shape meaning not only through expressions of empathy and respect for fallen soldiers, but also through the control of public interpretation, emphasis on moral values, and the building of national solidarity. By exposing the complex dynamics of legitimacy in political statements, this study makes a theoretical contribution to the understanding of discursive practices in political and methodological contexts by offering an applicable approach to the critical discourse analysis of political discourse and public communication more broadly.